European Climate Pact Ambassador Survey (ECPAS) [dataset] - Rzepka, David; Tosun, Jale (Universität, 2025)
This dataset contains the results from the European Climate Pact Ambassador Survey (ECPAS) based on 78 respondents. It contains socio-demographic background data of the European Climate Pact Ambassadors as well as information on their motivation and activities in the context of their mandate. The data was collected in November 2023.
Gesehen am 04.12.2025
Keywords: Forschungsdaten; Datenbank